Validity and reliability of the Cognitive Complaints in Bipolar Disorder Rating Assessment (COBRA) in Japanese patients with bipolar disorder. (August 2017) - Toyoshima, Kuniyoshi; Fujii, Yutaka; Mitsui, Nobuyuki; Kako, Yuki; Asakura, Satoshi; Martinez-Aran, Anabel; Vieta, Eduard; Kusumi, Ichiro
Abstract: In Japan, there are currently no reliable rating scales for the evaluation of subjective cognitive impairment in patients with bipolar disorder. We studied the relationship between the Japanese version of the Cognitive Complaints in Bipolar Disorder Rating Assessment (COBRA) and objective cognitive assessments in patients with bipolar disorder. We further assessed the reliability and validity of the COBRA. Forty-one patients, aged 16–64, in a remission period of bipolar disorder were recruited from Hokkaido University Hospital in Sapporo, Japan. The COBRA (Japanese version) and Frankfurt Complaint Questionnaire (FCQ), the gold standard in subjective cognitive assessment, were administered. A battery of neuropsychological tests was employed to measure objective cognitive impairment. Correlations among the COBRA, FCQ, and neuropsychological tests were determined using Spearman's correlation coefficient. The Japanese version of the COBRA had high internal consistency, good retest reliability, and concurrent validity—as indicated by a strong correlation with the FCQ. A significant correlation was also observed between the COBRA and objective cognitive measurements of processing speed. These findings are the first to demonstrate that the Japanese version of the COBRA may be clinically useful as a subjective cognitive impairment rating scale in Japanese patients with bipolar disorder. Highlights: The psychometric properties of the COBRA in Japanese bipolar patients are unknown. Test-retest reliability of the COBRA was confirmed in this patient population. The COBRA is valid and reliable for assessing subjective cognitive impairment.